2020
DOI: 10.1088/1758-5090/ab9907
|View full text |Cite
|
Sign up to set email alerts
|

Testicular organoid formation is a property of immature somatic cells, which self-assemble and exhibit long-term hormone-responsive endocrine function

Abstract: Testicular organoid models are tools to study testicular physiology, development, and spermatogenesis in vitro. However, few side-by-side comparisons of organoid generation method have been evaluated. Here, we directly tested whether the culture microenvironment is the prime determinant promoting testicular organoid self-assembly. Using Matrigel as a representative extracellular matrix (ECM), we compared multiple culture environments, 2D and 3D, ECM-free and ECM, for organoid self-assembly with immature murine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 88 publications
(125 reference statements)
5
34
0
Order By: Relevance
“…We have previously reported that de novo testis tubulogenesis can be induced by the in vivo implantation of primary testis cell aggregates, derived from neonatal piglets, under the skin of immunodeficient mice to form a compartmentalized testis tissue [ 36 , 37 ]. In the present study, we demonstrated that neonatal porcine testis cells also possess an in vitro tubulogenesis ability to form a compartmentalized testis organoid, similar to the reported mouse testis organoids [ 15 , 38 ]. Among various testis organoid culture systems, cell spheroid culture method has been proven effective in initiating the reconstruction of a compartmentalized testis organoid in rodent models [ 15 , 38 ].…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…We have previously reported that de novo testis tubulogenesis can be induced by the in vivo implantation of primary testis cell aggregates, derived from neonatal piglets, under the skin of immunodeficient mice to form a compartmentalized testis tissue [ 36 , 37 ]. In the present study, we demonstrated that neonatal porcine testis cells also possess an in vitro tubulogenesis ability to form a compartmentalized testis organoid, similar to the reported mouse testis organoids [ 15 , 38 ]. Among various testis organoid culture systems, cell spheroid culture method has been proven effective in initiating the reconstruction of a compartmentalized testis organoid in rodent models [ 15 , 38 ].…”
Section: Discussionsupporting
confidence: 85%
“…In the present study, we demonstrated that neonatal porcine testis cells also possess an in vitro tubulogenesis ability to form a compartmentalized testis organoid, similar to the reported mouse testis organoids [ 15 , 38 ]. Among various testis organoid culture systems, cell spheroid culture method has been proven effective in initiating the reconstruction of a compartmentalized testis organoid in rodent models [ 15 , 38 ]. This methodology allows cells to be freely suspended in the media instead of being attached to the walls of the culture well.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations